2016
DOI: 10.1097/hjh.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

Night-time home versus ambulatory blood pressure in determining target organ damage

Abstract: In untreated hypertensives, night-time BP assessed by home monitoring appears to be as good as night-time ambulatory monitoring in determining preclinical target organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In regard to the associations between nocturnal home BP and hypertensive target organ damages (TODs), we demonstrated that nocturnal home SBP levels were significantly correlated with the urinary albumin/creatinine ratio (UACR), left ventricular mass index (LVMI), and brachial‐ankle pulse wave velocity (baPWV) even after adjustment for morning, evening, and office BP levels 15 . Studies comparing the association of hypertensive TOD with nocturnal BP measured by HBPM and the association of hypertensive TOD with nocturnal BP measured by ABPM reported that the correlation coefficient between nocturnal home SBP and UACR was significantly greater than that for the relationship between nocturnal ambulatory SBP and UACR 23,24 . This result is likely attributed to the superiority of nocturnal BP measured by HBPM compared with nocturnal BP measured by conventional ABPM in terms of measurement frequency, reproducibility, and acceptability.…”
Section: Nocturnal Home Blood Pressure Monitoringmentioning
confidence: 99%
“…In regard to the associations between nocturnal home BP and hypertensive target organ damages (TODs), we demonstrated that nocturnal home SBP levels were significantly correlated with the urinary albumin/creatinine ratio (UACR), left ventricular mass index (LVMI), and brachial‐ankle pulse wave velocity (baPWV) even after adjustment for morning, evening, and office BP levels 15 . Studies comparing the association of hypertensive TOD with nocturnal BP measured by HBPM and the association of hypertensive TOD with nocturnal BP measured by ABPM reported that the correlation coefficient between nocturnal home SBP and UACR was significantly greater than that for the relationship between nocturnal ambulatory SBP and UACR 23,24 . This result is likely attributed to the superiority of nocturnal BP measured by HBPM compared with nocturnal BP measured by conventional ABPM in terms of measurement frequency, reproducibility, and acceptability.…”
Section: Nocturnal Home Blood Pressure Monitoringmentioning
confidence: 99%
“…When < 70% of 24 h readings were achieved, further investigation was undertaken of edited day-time and night-time readings. Day-time or night-time measurements that did not pass validity criteria for the time period (day-time: 20 valid readings; night-time: 7 valid readings) were discarded and excluded from the final analyses by a process described in similar studies [51,53]. All valid day-time and night-time readings were averaged to provide a single day-time and night-time ABP value per study participant [53].…”
Section: Methodsmentioning
confidence: 99%
“…1 However, recent technological advances in self-monitoring devices have facilitated the development of several kinds of home measurement devices for nocturnal BP, and a number of studies have shown that nocturnal HBPM is both feasible and effective. 8,[57][58][59][60][61][62][63][64][65] The first data on nocturnal BP measurement were obtained in 2001, when a Japanese research group examined the impact of a single nocturnal BP measurement on sleep quality. 63 The same research group later found that the reproducibility of a single nocturnal BP measurement as assessed using an HBPM device was not good.…”
Section: The Role Of Home Blood Pressure Monitoring In the Diagnosis mentioning
confidence: 99%
“…[ 60 ] Another study (n=30) evaluating nocturnal BP of treatment-naive individuals using an HBPM device found that night-time BP measurements were significantly lower in subjects without left ventricular hypertrophy (LVH) compared with those with LVH, while daytime readings were not significantly different between the two groups. [ 62 ] A recent meta-analysis found that the nocturnal HBPM and ABPM measurements provided similar values (HBPM readings were 1.4 mmHg higher for systolic and 0.2 mmHg lower for diastolic values) compared with ABPM measurements, and both were similarly associated with measures of target organ damage (left ventricular mass index). [ 58 ]…”
Section: The Role Of Home Blood Pressure Monitoring In the Diagnosis mentioning
confidence: 99%